PEMBELAJARAN BERDIFERENSIASI PADA KERAGAMAN KARAKTERISTIK PESERTA DIDIK DALAM PEMENUHAN TARGET KURIKULUM - Arif Bima Fajar Wahyudi; Darmawan, Puguh Darmawan (Guruku: Jurnal Pendidikan Profesi Guru, 2024)
This study aims to collect various literature reviews and explain concepts related to differentiated learning to fulfill curriculum targets with a diversity students. Differentiated learning involves managing, monitoring, assisting, and guiding students' activities based on their individual learning profiles, readiness, and interests. The method used in writing this article is a literature review study from articles, journals, books, the internet, and other literary sources. The findings of the literature review demonstrate that the aim of differentiated learning to coordinate learning by paying attention to learning interests, learning readiness and learning preferences, accommodating students so that learning objectives can be achieved by all students, increasing motivation and learning outcomes, establishing teacher and student interaction and building attitudes appreciate diversity. The conclusion drawn is that differentiated learning offers opportunities for students to learn effectively and naturally with teachers capable of employing suitable methods and approaches.